SAP HCM - a complete tutorial : deploy and implement the diverse functionalities of SAP HCM - Karthik S, Ganesh (Professional expertise distilled., 2014)
This book is a simple tutorial guide with practical issues and their solutions, aimed at enabling readers to implement the various features of the SAP HCM module. If you are familiar with ERP products, and would like to leverage knowledge and fine-tune your configuration skills, then this book is for you. This book is aimed at readers who want to learn about SAP HCM and its most popular functionalities.